2016
DOI: 10.3389/fpsyg.2016.00730
|View full text |Cite
|
Sign up to set email alerts
|

Can Birds Perceive Rhythmic Patterns? A Review and Experiments on a Songbird and a Parrot Species

Abstract: While humans can easily entrain their behavior with the beat in music, this ability is rare among animals. Yet, comparative studies in non-human species are needed if we want to understand how and why this ability evolved. Entrainment requires two abilities: (1) recognizing the regularity in the auditory stimulus and (2) the ability to adjust the own motor output to the perceived pattern. It has been suggested that beat perception and entrainment are linked to the ability for vocal learning. The presence of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 59 publications
(104 reference statements)
2
34
2
Order By: Relevance
“…50 More recent studies have questioned an explicit link between vocal learning and beat perception 32,51 or have suggested at least a graded scale in avian species. 21 Some bird species appear to attend more strongly to specific local features of the individual stimuli (e.g., the interval between two onsets) rather than the overall regularity (or isochrony) of the stimuli, a main feature attended to by human listeners. 52 These findings seem to call for a reexamination of the nature and mechanisms underlying rhythmic cognition and its core components, such as isochrony and beat perception.…”
Section: Macaquementioning
confidence: 99%
“…50 More recent studies have questioned an explicit link between vocal learning and beat perception 32,51 or have suggested at least a graded scale in avian species. 21 Some bird species appear to attend more strongly to specific local features of the individual stimuli (e.g., the interval between two onsets) rather than the overall regularity (or isochrony) of the stimuli, a main feature attended to by human listeners. 52 These findings seem to call for a reexamination of the nature and mechanisms underlying rhythmic cognition and its core components, such as isochrony and beat perception.…”
Section: Macaquementioning
confidence: 99%
“…Potential candidates for the basic components of musicality that have been proposed in the recent literature are relative pitch (e.g., contour and interval analysis; Justus & Hutsler, 2005;Trehub, 2003), regularity and beat perception (Honing, 2012;ten Cate et al, 2016), tonal encoding of pitch (Hoeschele, Cook, Guillette, Hahn, & Sturdy, 2014;Peretz & Coltheart, 2003), and metrical encoding of rhythm (Fitch, 2013b;Winkler, Háden, Ladinig, Sziller, & Honing, 2009). Some of these musical traits may be common to humans and other species, and others might be uniquely human (see figure 1.4).…”
Section: Core Components Of Musicalitymentioning
confidence: 99%
“…With regard to rhythmic cognition in primates, the empirical evidence Honing et al, under review; With regard to rhythmic cognition in birds, the literature remains partial and divided. Initially a causal link between vocal learning and beat perception and synchronization was proposed (Patel, 2006;, associated with evolutionary modifications to the basal ganglia that play a key role in mediating a link between auditory input and motor output during learning (Petkov & Jarvis, 2014); however, other studies have questioned such an explicit link Wilson & Cook, 2016) or suggested at least a graded scale in avian species (ten Cate et al, 2016). Some species attend more strongly to specific local features of the individual stimuli (e.g., the exact duration of time intervals) rather than the overall regularity of the stimuli, a main feature human listeners attend to; van der Aa, Honing, & ten Cate, 2015).…”
Section: Probing Rhythmic Cognitionmentioning
confidence: 99%
“…However, their results, such as evidence of the entrainment of animals to music stimuli [17,18], have great significance for our study. These kinds of test devices have enabled scientists to gather evidence that animal species have auditory skills and musical talents, and examine how these skills work [15,16].…”
Section: Cultural Contextmentioning
confidence: 99%
“…Therefore, the music should be attuned to the animals' auditory skills. Studies have shown that non-human species also have musical skills [14][15][16] and display entrainment to auditory stimuli [17,18]. Animal species such as grey parrots, cockatoos, elephants, primates, pigeons, and carps have been found to be able to discriminate between different composers or different genres, prefer music to silence, or move in rhythmic synchronicity to the musical beat [10,14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%